2001
DOI: 10.1038/sj.ejcn.1601218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of palm oil and dietary cholesterol on plasma lipoproteins: results from a dietary crossover trial in free-living subjects

Abstract: Objective: To study the effects of palm oil (PO) and egg consumption (E) on plasma lipoproteins. Design: Randomized crossover trial. Setting: Free-living subjects. Subjects: Twenty-eight healthy male students aged 20 -34 y. Interventions: Four typical Colombian diets (10 878 kJ=day; 57% energy in carbohydrates, 12% energy in proteins and 31% energy in fats) were consumed for 4 weeks. The HPOLC diet was high in PO (8.8% energy as palmitic acid, PA) and low in eggs (181.2 mg=kJ of dietary cholesterol, DC); the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
2
5
0
1
Order By: Relevance
“…For LDL-c, a non-extreme short-term intervention (16 weeks) of daily cholesterol consumption led to increased LDL-c. This result was consistent with another study [30]. Thus, people with borderline high LDL-c level should restrict their egg consumption.…”
Section: Overall Completeness and Applicability Of The Evidencesupporting
confidence: 93%
See 2 more Smart Citations
“…For LDL-c, a non-extreme short-term intervention (16 weeks) of daily cholesterol consumption led to increased LDL-c. This result was consistent with another study [30]. Thus, people with borderline high LDL-c level should restrict their egg consumption.…”
Section: Overall Completeness and Applicability Of The Evidencesupporting
confidence: 93%
“…On the contrary, our study tried to avoid bias from conceptual heterogeneity by focusing on healthy subjects. For instance, the best synthesis in recent years included trials by Bautista et al [30] and Schwab et al [64], but we did not include those trials because they recruited patients with diabetes or hypercholesterolemia [9]. Thus, pooled results in the present study may be more precise and our findings may be more appropriate for healthy population.…”
Section: Comparison To Previous Synthesesmentioning
confidence: 91%
See 1 more Smart Citation
“…L'effet de l'huile de palme est modul e aussi par l'apport en cholest erol, avec une interaction entre le % de lipides et d'AG satur es et le cholest erol alimentaire. Lorsque l'apport en cholest erol alimentaire est tr es faible et l'apport en lipides bas (Ghafoorunissa et al, 1995), l'huile de palme n'a pas d'effet ; lorsque l'apport en cholest erol est faible mais l'apport en lipides est extrêmement elev e (Cater et al, 1997), l'huile de palme el eve le C-LDL ; lorsque l'apport en cholest erol alimentaire est tr es elev e (Bautista et al, 2001), l'effet hypercholest erol emiant de l'huile de palme augmente.…”
Section: Dans Le Cadre D'un R Egime Normolipidique (35-40 %)unclassified
“…Dietary intake of PKO could pose a risk for coronary artery disease on a long term basis [10]. It was suggested that non-extreme short-term changes in PO and dietary cholesterol consumption lead to significant elevations in plasma TC and LDL-C in humans [11]. PO and PKO should be classified as cholesterol-raising fats for humans [12].…”
Section: Introductionmentioning
confidence: 99%